ONLINE REPURCHASE INTENTION ON MARKETPLACE: PRODUCT QUALITY, CUSTOMER SERVICE, EASE OF USE, TRANSACTION SECURITY, PRICE - Refan Hidayat Agseftama; Eny Kusumawati (ITB AAS Indonesia Surakarta, 2025)
Online repurchase intention refers to consumers’ willingness or tendency to make repeat purchases of products or services through online platforms following previous buying experiences. This research to analize the impact of factors such as product quality, customer service, ease of use, transaction security, and price on online repurchase intention among students of the Faculty of Economics and Business Muhammadiyah University of Surakarta within marketplace platforms. Using a simple random sampling technique, 100 students have met the criteria were selected as the observation units. Multiple linear regression analysis was employed to analyze the data. The findings provide empirical evidence that transaction security and price have a significant impact on repurchase intention in the marketplace, whereas product quality, customer service, and ease of use do not significantly affect repurchase intention. Keywords: Repurchase Intention, Product uality, Customer Service, Ease of Use, Transaction Security, Price